Comparison of hepatocellular carcinoma in Eastern versus Western populations. Issue 22 (13th September 2016) - Choo, Su Pin; Tan, Wan Ling; Goh, Brian K. P.; Tai, Wai Meng; Zhu, Andrew X.
Abstract : Hepatocellular carcinoma (HCC) is a heterogeneous disease that remains highly prevalent in many Asian countries and is the second most common cause of cancer‐related mortality worldwide. Significant differences exist between Eastern and Western populations on many key aspects of HCC, contributing to the potential different treatment outcomes and challenges of clinical trial design and data interpretation. In this review, the authors compare HCC in Asia versus the West and highlight 1) differences in terms of epidemiology and trends and their correlation with etiology, 2) differences in genetics and how they relate to underlying etiology, 3) differences in treatment approaches based on existing guidelines and consensus statements, and 4) differences in clinical outcomes for Asian versus non‐Asian patients with HCC in clinical trials and the implications for future clinical trial design. Cancer 2016;122:3430–3446 . © 2016 American Cancer Society Abstract : Significant differences exist between Eastern and Western populations on many key aspects of hepatocellular carcinoma, contributing to potentially different treatment outcomes. These differences are highlighted in terms of epidemiology, genetics, treatment approaches, and outcomes for Asian versus non‐Asian patients with hepatocellular carcinoma and their implications for clinical trial design and interpretation.